BOARDING SCHOOL MANAGEMENT OF MADRASAH LIYAH NEGERI 2 SERANG - Nana Suryapermana; Anis Fauzi; Yahdinil Firda Nadhiroh (UIN Sumatera Utara Medan, 2021)
The main problem in this research is how Boarding School Management of Madrasah Aliyah Negeri 2 Serang. This study aims to find and describe the content of policies, planning, management, problems, supporting factors, results achieved, and how to resolve the problems in the Implementation of Boarding School in MAN 2 Serang. This study used qualitative descriptive method approach, which is related to data collection, which aims to describe the condition and situation in Madrasah Aliyah Negeri 2 Serang. Data collection techniques used are interview, observation, documentation, and triangulation. Boarding School is an integrated educational institution between general education and 'pesantren' education as supporting of teaching learning activity in Madrasah. The aim of implementing more advance and comprehensive education, holistic, the world of science can be achieved and religious knowledge can be mastered. Boarding School management system in MAN 2 Serang is a 'semi-pesantren' system, where all students are required to live in Boarding.